THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND WORK DISCIPLINE TOWARD JOB SATISFACTION AND THE PERFORMANCE OF COOPERATION EXTENSION OFFICER OF EAST JAVA’S STATE MINISTER FOR COOPERATIVES SMALL AND MEDIUM ENTERPRISES (SME) - Lukman Hakim, Diana Sulianti K Tobing & Istifadah (International Journal of Research Science and Management, 2019)
In various fields, especially organizational life, human factors are the main problem in every activity in it. To find out the extent of the role and contribution of human resources in achieving organizational success, performance measurement is certainly needed. The purpose of this study is to examine the effect of Transformational Leadership Style and Work Discipline on Job Satisfaction and Employee Performance. This research is a review of the theory and several studies which have been conducted on the Style of Transformational Leadership, Work Discipline, Job Satisfaction, and Employee Performance. The results of the study became a reference to improve Employee Performance related to Transformational Leadership Style, Work Discipline and Job Satisfaction.